Influence of sanitary policies on health care cost containment in Chile - Barahona-Urbina, Planck (2011)
Introduction: The literature on economics proposes different provider payment mechanisms at hospitals in order to obtain incentives in health care cost containment. Objectives: To analyze the theoretical foundations of implemented cost restraint instruments, payment associated to diagnosis (PAD), and payment for valued assistance (PFV) during the last two decades and their effectiveness on the Chilean sanitary system. Design: Econometric and non parametric analysis. Setting: Chile. Materials: Data from Chile’s Ministry of Health and the National Health Fund was used. Interventions: Application of time series methodology, data envelopment analysis and multinomial logit model to detect whether payment mechanisms have had the desired effect on cost containment. Main outcome measures: Effects of hospital payment system. Results: Results have shown that the second payment system, in addition to not creating incentives in average stays reduction nationally it has neither generated higher levels of efficiency. Conclusions: The first payment system had a positive effect in curbing resources use. The second mechanism of payment generated neither incentives in the reduction of average stay in the country nor higher levels of efficiency. That is to say, not only more resources are used but also it is possible that the system is acting in a wicked way making difficult to take measures that favors efficiency.